Fat Suppression with Dixon Techniques in Musculoskeletal Magnetic Resonance Imaging: A Pictorial Review - Guerini, Henri; Omoumi, Patrick; Guichoux, François; Vuillemin, Valérie; Morvan, Gérard; Zins, Marc; Thevenin, Fabrice; Drape, Jean Luc (Seminars in Musculoskeletal Radiology, 2015)
Dixon techniques are part of the methods used to suppress the signal of fat in MRI. They present many advantages compared with other fat suppression techniques including (1) the robustness of fat signal suppression, (2) the possibility to combine these techniques with all types of sequences (gradient echo, spin echo) and different weightings (T1-, T2-, proton density-, intermediate-weighted sequences), and (3) the availability of images both with and without fat suppression from one single acquisition. These advantages have opened many applications in musculoskeletal imaging. We first review the technical aspects of Dixon techniques including their advantages and disadvantages. We then illustrate their applications for the imaging of different body parts, as well as for tumors, neuromuscular disorders, and the imaging of metallic hardware.
Keywords: magnetic resonance imaging; fat suppression technique; fat; muscles; tendons; bone marrow; metal artifacts; tumor; joint